Implementasi Sistem Informasi Pembelajaran Berbasis E-Learning Studi Kasus (SMK Nuurul Bayan Kalapanunggal Sukabumi) - Nining Suryani; Jaenudin Jaenudin (Jurnal Informatika dan Bisnis, 2013)
Vocational School Nuurul Bayan Kalapanunggal located in Sukabumi District , is one of the schools that use conventional learning methods , which can only be done on condition that the meetings between students and teachers in the classroom . This leads to a bottleneck in the provision and delivery of such materials , discussions and provision of training to the students . In addition to face-to -face learning in class sometimes have problems that result in the learning process becomes disrupted by the absence of teachers and learners in the classroom . So in need of a new system that can support teaching and learning activities , one of which is online learning or e -learning . This online learning system using uml as waterfalls and design e-learning design to be built . In this system there is a feature for the distribution of materials , assignments , exercises , tutorials and other information related to school activities , which is expected to help students learning activities because with this system , students can access the learning activities are not only limited in only in the classroom but can be anywhere.